CENTRAL BANK DIGITAL CURRENCY: LESSONS LEARNT FROM THE SAND DOLLAR - Nguyen, Thuy Minh * (Graduate Program of Universitas Tarumanagara, 2024)
This research examines the implemention of the Sand Dollar in the Bahamas and draws several suggestions for policy makers when considering this new type of money in order to achieve the objectives. Besides, this study also provides basic insight into the background of development and motivations for this currency around the world. The study points out that the authorities need to promote more educational programs to introduce and bring more knowledge of the benefits of this currency and re-consider the non-interest bearing feature as it might be less appealing for holders.